rac-2-(2′-Ferrocenyl-2′-hydroxy-n-propyl)-1,3-benzothiazole - Martin G. Zhen; Kathleen L. May; Robert A. Gossage (Molbank)
The synthesis and characterisation (UV-Vis, IR, HRESI-MS, 1H and 13C NMR spectroscopies, electrochemistry) is reported of the novel title material (1: alternatively named rac-1-(2′-benzothiazolyl)-2-ferrocenyl-2-propanol): a rare example of a ferrocenyl-benzothiazole hybrid species. Compound 1 is produced by the low temperature reaction of acetylferrocene (3) with a solution of the methyl anion derived via the deprotonation of 2-methyl-1,3-benzothiazole. The yield of 1 is moderate (34%) after purification and is an air and thermally stable solid under ambient conditions. Attempts to sublime 1, however, result in decomposition with one of the products being identified (NMR) as 3. The spectroscopic features of 1 are presented. Attempts to obtain suitable crystalline material of 1 for a single crystal X-ray diffraction study were unfortunately unsuccessful. Compound 1 also does not form stable coordination complexes with various metal salts (e.g., Ni[2+], Co[2+], etc.) under the conditions tested.